2015
DOI: 10.1016/j.apjtm.2015.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Influence of overexpression of SOCS2 on cells of DN rat

Abstract: The overexpression of SOCS2 can decrease the expression of inflammatory cytokines and fibrosis related proteins in DN rats and cells, and meanwhile suppress the activation of JAK/STAT signaling pathway mediated by DN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 14 publications
2
8
0
Order By: Relevance
“…TAK-242 and PDTC both conspicuously suppressed apoptosis and inflammatory cytokines production in HG-stimulated podocytes; moreover, either TAK-242 or PDTC strengthened the inhibitory influence of SOCS2 overexpression on apoptosis and inflammatory cytokines, indicating that SOCS2 overexpression repressed apoptosis and inflammatory cytokines production by inhibiting the TLR4/NF-κB signaling pathway in HG-stimulated podocytes. Additionally, upregulation of SOCS2 has been demonstrated to suppress JAK/STAT and EPK signaling pathways induced by STZ in rat kidneys [ 9 , 24 ], consistent with our present results. Our study demonstrated that SOCS2 overexpression showed a stronger inhibitory effect on the TLR4/NF-κB pathway than the JAK/STAT pathway in HG-stimulated podocytes.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…TAK-242 and PDTC both conspicuously suppressed apoptosis and inflammatory cytokines production in HG-stimulated podocytes; moreover, either TAK-242 or PDTC strengthened the inhibitory influence of SOCS2 overexpression on apoptosis and inflammatory cytokines, indicating that SOCS2 overexpression repressed apoptosis and inflammatory cytokines production by inhibiting the TLR4/NF-κB signaling pathway in HG-stimulated podocytes. Additionally, upregulation of SOCS2 has been demonstrated to suppress JAK/STAT and EPK signaling pathways induced by STZ in rat kidneys [ 9 , 24 ], consistent with our present results. Our study demonstrated that SOCS2 overexpression showed a stronger inhibitory effect on the TLR4/NF-κB pathway than the JAK/STAT pathway in HG-stimulated podocytes.…”
Section: Discussionsupporting
confidence: 92%
“…Zhou et al reported that SOCS2 attenuated STZ-induced renal lesions including renal/glomerular hypertrophy, glomerular hyperfiltration, aberrant inflammation and fibrosis and reduced the levels of proinflammatory proteins (TGF-β, collagen IV and fibronectin) in DN [ 25 ]. Bao et al found that SOCS2 overexpression decreased the increased expressions of inflammatory cytokines (MCP-1, TNF-α and IL-6) and fibrosis related protein in STZ-induced DN rats [ 9 ]. Consistently, our study showed that SOCS2 overexpression significantly increased the body weight and dramatically decreased the 24-h proteinuria which is a significant clinical hallmark of early stage DN, blood glucose level, serum creatinine and blood urea nitrogen in DN rats, alleviating diabetic renal injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…e overexpression of SOCS2 could decrease the expression of inflammatory cytokines [26,27]. SOCS2 knockout or deficiency led to increasing nuclear factor κB (NF-κB) activity as well as elevated expression of genes for the inflammatory cytokines [25,28].…”
Section: Discussionmentioning
confidence: 99%
“…SOCS2 was involved in hyperglycaemia and glucose intolerance caused by the abnormal regulation of proinsulin processing and insulin secretion in beta cells [13]. The overexpression of SOCS2 possess the protective function in the development of diabetic nephropathy by reducing the expression of in ammatory cytokines and suppressing the activation of JAK/STAT pathway [14]. These physiological studies proposed that SOCS2 might play an important role in diabetes, but the role of genetic polymorphism within SOCS2 gene for T2DM predisposition has been less studied.…”
Section: Introductionmentioning
confidence: 99%